3D Muscle Architecture of the Pectoral Muscles of European Starling (Sturnus vulgaris). Issue 1 (1st February 2019) - Sullivan, S P; McGechie, F R; Middleton, K M; Holliday, C M
Abstract: Avian flight is achieved through a number of modifications to the body, including the pectoral girdle, yet little is known about the architecture of the pectoral musculature. Muscle architecture is a critical variable in determining the biomechanical function of the vertebrate musculoskeletal system; however, accurate three-dimensional (3D) understanding of muscle architecture has been historically difficult to acquire. Here, we present a musculoskeletal model of a European starling ( Sturnus vulgaris ) pectoral girdle generated from iodine contrast-enhanced micro-computed-tomography (CT) data and 3D fiber tracking analysis. We used a template-based fiber-tracking algorithm to reconstruct muscle fibers in 3D based on grayscale differences in CT images, which allowed us to estimate fascicle lengths, pennation angles, muscle volumes, and physiological cross-sectional area. Our modeled muscles were qualitatively accurate; however, quantitative muscle architecture data differed between digital and traditional gross-dissection methods reflecting the complex organization of the tissue and differing natures of data collection. We found that model quality is affected by the resolution of CT image data and the fiber-tracking program's input parameters. Nonetheless, digital fiber tracking offers numerous advantages over gross-dissection methods, most importantly, the ability to visualize and quantify entire muscles in three-dimensions, yielding a much more accurate estimation of whole muscle architecture.